Pengaruh Metode Two Stay Two Stray Terhadap Hasil Belajar Lompat Jauh Siswa Kelas VII MTS Al-Ikhsan Betung - Wahyudi, Muhammad Ferdi; Daryono, Daryono; Fajar, Mutiara (Institut Teknologi Pendidikan Indonesia, 2023)
The problem in this study was learning that was found to jump far which still had not been completed learning outcomes. This study aims to determine the effect of the two by two stray method on the long jump learning outcomes of class VII students of MTS Al-Ikhsan Betung. The research method used in this study is an experimental method with the type of one-group pretest-posttest design. The research sampleconsisted of 22 people using the total population technique. The data collection technique was carried out using a psychomotor performance test. Research data analysis techniques using paired-samples t-test. Based on the research findings and analysis of research data, this study concludes that there is an effect of the two staytwo stray methods on the long jump learning outcomes of class VII MTS Al-Ikhsan Betung because t-count > t-table (6.548 > 1.72).